Effects of Pilates exercises in anthropometric and hemodynamic parameters from subjects with chronic nonspecific low back pain: randomized clinical trial (Research, Society and Development, 2020)
Introduction: Exercises of the Pilates method have been used as a resource to modify anthropometric and hemodynamic parameters, besides reducing the intensity of nonspecific chronic low back pain (NSCLBP). Objective: To evaluate the behavior of anthropometric and hemodynamic parameters and pain intensity in individuals with NSCLBP submitted to a protocol of Pilates exercises on the ground or to a transcutaneous electrical nerve stimulation (TENS). Methodology: This is a randomized clinical trial with 36 individuals with NSCLBP from both sexes aged between 18 and 59 years. Subjects were randomly allocated to the control group (GC; n=17), treated by TENS and Pilates exercise group (EG; n=19). The primary outcomes were anthropometric measures and body fat percentage. The secondary outcomes were pain intensity, assessed by visual analogue scale (VAS), systolic blood pressure (SBP), diastolic blood pressure (DBP) and resting heart rate (RHR). Results: No difference between groups were identified in the comparative analysis for the anthropometric data (P>0.05). There was a significant reduction (P